Generation of tribenuron‐methyl herbicide‐resistant OsCYP81A6‐expressing rapeseed (Brassica napus L.) plants for hybrid seed production using chemical‐induced male sterility. Issue 3 (1st April 2016) - Yao, Xuan; Wang, Yaqin; Yue, Xiaopeng; Liu, Meng; Liu, Kede
Abstract: Chemical‐induced male sterility (CIMS) is a method for hybrid rapeseed ( Brassica napus L.) production. Some sulphonylurea herbicides such as tribenuron‐methyl (TBM) are used as chemical hybridization agents (CHAs) in CIMS systems. However, the male parents must be protected from herbicide injury with a shield during spraying of the female parents with CHAs to induce male sterility. Thus, using herbicide‐resistant rapeseed lines as the male parents can significantly simplify the seed production procedure and reduce the cost in hybrid seed production. A rice cytochrome P450 hydroxylase, OsCYP81A6, has been previously characterized to confer resistance to bentazon and sulphonylurea herbicides. We demonstrate here that the introduction of OsCYP81A6 renders rapeseed plants resistant to TBM. Compared with wild‐type plants, the transgenic plants displayed normal stamen development and male fertility when treated with 0.05 mg/l of TBM, the dose used for inducing male sterility in hybrid seed production. These results indicate that the OsCYP81A6 ‐expressing rapeseed plants can be used as the male parents for hybrid rapeseed production using CIMS.